(3OjhGf GdCNQS GdHZOGOjs - (3YHO GdZaGQ Hf YHO GdhGMO Hf hgH GdGNQS GdehUdj,J (B1290 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI(B: (3dYHOGdZaGQ GdTgjQ HGdCNQS aj eOM GdSjO EHQGgje CafOj GdQaGYj GdHUQj(B: (3gGJgG MeQGA JMcj GdYfOeG hGSbfjgG ef jOj YPH Gddei s
(3BNQgG (B:s
(3ef bUjOI OGdjI bGd LGeYI CXfgG aj eOM GdTjN eOMJ fhQ heSJLeY ddLhO EPG eG OYhJg OYhJ eLjHkG bO JgjkG hGYJOi s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B21 s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI GdMceI HHZOGO (B(98) s
Keywords: (3GdCOHs